8 - Youth Employment and Large-scale Agricultural Land Investments in Africa: Mixed-Method Insights from Nigeria: Alhassan Karakara, Uchenna Efobi, Ibukun Beecroft, Felicia Olokoyo & Evans Osabuohien - Karakara, Alhassan; Uchenna Efobi, Uchenna Efobi; Beecroft, Ibukun; Olokoyo, Felicia; Osabuohien, Evans (Africa Development, 2021)
This study examines the linkage between youth employment and large-scale agricultural land investment (LALI) in Africa with a focus on Nigeria. There is no consistent direction regarding the effects of LALIs on employment in the literature. While some studies found a positive effect, others opine that LALIs could have a deteriorating effect. This study contributes to the discourse by carrying out a comparative analysis of youth (un)employment in communities with and without LALIs. A mixed methods analysis is engaged in the study. The quantitative data is estimated using the difference-in-difference and propensity score matching techniques, while the qualitative aspect is carried out using key informant interviews and focus group discussion. The quantitative result shows that the presence of LALIs in the communities leads to a 1.24 percentage reduction in the amount of wage earned by the youth, but was only significant at 10 per cent. On the employment of youth conditioned upon the presence of LALIs in a community, the study finds a reduction in the number of hours worked by six hours, which was also only significant at 10 per cent. From the qualitative analysis, the study finds varied wage levels across the sample. These findings raise concerns regarding the type of employment provided by LALIs. Hence, to curb youth unemployment and create decent jobs, LALI recipient countries could promote bette bargaining power for the host communities to negotiate better employment.